Application of Digital Pentapartioned Neutrosophic Set in MCDM for Pregnancy Health Care via Digital Pentapartitioned Neutrosophic Borda Approach - R. Shalini; Dr. S. Nagarani; Dr. G. Sindhu (Utilitas Mathematica, 2025)
In many different domains, neutrosophic sets naturally address uncertainties using a fresh, pretty mathematical technique. Today, it largely and successfully fixes problems in real life. We give a general overview of the Digital Pentapartitioned Neutrosophic Borda Algorithm before going into greater detail about its complexity. The main health problem and the most frequent cause of pregnancy-related health problems in women may be identified by combining borda count with digital pentapartitioned neutrosophic set in digital topological spaces.